Elucidation of the Translation Initiation Factor Interaction Network of Haloferax volcanii Reveals Coupling of Transcription and Translation in Haloarchaea - Schramm, Franziska; Borst, Andreas; Linne, Uwe; Soppa, Jörg (Frontiers in Microbiology, 2021)
Translation is an important step in gene expression. Initiation of translation is rate-limiting, and it is phylogenetically more diverse than elongation or termination. Bacteria contain only three initiation factors. In stark contrast, eukaryotes contain more than 10 (subunits of) initiation factors (eIFs). The genomes of archaea contain many genes that are annotated to encode archaeal homologs of eukaryotic initiation factors (aIFs). However, experimental characterization of aIFs is scarce and mostly restricted to very few species. To broaden the view, the protein-protein interaction network of aIFs in the halophilic archaeon Haloferax volcanii has been characterized. To this end, tagged versions of 14 aIFs were overproduced, affinity isolated, and the co-isolated binding partners were identified by peptide mass fingerprinting and MS/MS analyses. The aIF-aIF interaction network was resolved, and it was found to contain two interaction hubs, 1) the universally-conserved factor aIF5B, and 2) a protein that has been annotated as the enzyme ribose-1,5-bisphosphate isomerase, which we propose to rename to aIF2Bα. Affinity isolation of aIFs also led to the co-isolation of many ribosomal proteins, but also transcription factors and subunits of the RNA polymerase (Rpo). To analyze a possible coupling of transcription and translation, seven tagged Rpo subunits were overproduced, affinity isolated, and co-isolated proteins were identified. The Rpo interaction network contained many transcription factors, but also many ribosomal proteins as well as the initiation factors aIF5B and aIF2Bα. These results showed that transcription and translation is coupled in haloarchaea, like in Escherichia coli. It seems that aIF5B and aIF2Bα are not only interaction hubs in the translation initiation network, but also key players in the transcription-translation coupling.